On- and Off-Domain Cognitive Performance of Experienced Hearing Aid Users in Background Noise. - Lander, Devan M.; Baxter, Jodi; Roup, Christina M. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Hearing aid use in older adults has been suggested to reduce cognitive load, thereby improving performance on auditory-based cognitive tasks. However, there is limited research regarding how hearing aids impact performance during cognitively demanding auditory and visual tasks. The purpose of this study was to investigate the impact of advanced-level hearing aid use during auditory (on-domain) and visual (off-domain) cognitive tasks in background noise. Method: Thirty-one older adults aged 60–87 years participated in the study. All participants were experienced and satisfied hearing aid users. Participants were fitted with a study hearing aid to ensure consistent signal processing characteristics. A series of six cognitive tasks were completed in quiet and background noise with and without hearing aids. The visual tasks included the Trail Making Test, Stroop Color Word Test, and Size Comparison Span Test. The auditory tasks were the Oral Trail Making Test, Auditory Stroop Task, and Word Auditory Recognition and Recall Measure. Results: Results indicated that, for measures of inhibition, executive function, and attention, there was no significant benefit to the use of hearing aids. In contrast, hearing aid use resulted in better performance on working memory tasks. Conclusions: Results indicated that the benefit from hearing aids for auditory (on-domain) and visual (off-domain) cognitive task performance was mixed. Older adults performed better in quiet than in noise with and without hearing aids. Furthermore, hearing aids were beneficial in quiet environments when the working memory task was auditory (on-domain). The findings from the current study support that the use of hearing aids improves access to working memory in both quiet and noisy conditions, which may ultimately improve speech understanding.